The Influence of Audit Findings and Follow-Up of Audit Recommendations on The Level of Fraud in Government Agencies in Indonesia - Kurniawan, Fillosius Ronny; Avianti, Ilya; Irawady, Cahya (International Journal Labs, 2025)
The phenomenon of high fraud in financial reports in government agencies, both central and regional, is the focus of this study. This study also examines the effectiveness of audits by the BPK through audit findings and follow-up to audit recommendations in detecting and preventing or correcting fraud. This study uses a quantitative approach with panel data from 140 government agencies over 10 years. It examines the relationship between exogenous variables—audit findings and follow-up to audit recommendations, non-compliance, and weaknesses of the Internal Control System (ICS)—and the endogenous variables of fraud levels related to asset misappropriation and financial reporting, using STATA. Additionally, this study explores the role of audits in detecting and preventing or correcting fraud. Path analysis is also employed to test the correlation between exogenous variables and their influence on endogenous variables. The results prove that audit findings and follow-up to audit recommendations have, simultaneously, been effective in detecting and significantly influencing the level of fraud. However, partially, audit findings have been effective in detecting and significantly affecting the level of fraud, whereas follow-up to audit recommendations is not effective in detecting fraud but has a significant effect on the level of fraud.